Culturas juvenis e educação física no contexto de uma escola pública de Belo Horizonte: um estudo de caso - Parrela, Galeno Criscolo (2011)
The paths taken by young people in the spaces of the contemporary world have been measured by different opportunities at school, work, leisure and culture that eventually have set standards for their lives. The ways that they use their bodies, tattoos, body piercing, earrings, hats and settling their hair with it´s flippancy hair and tones, the way they dress up, listen to music, dance, exchanging glances, greetings and space / time that they share in school and out of it, help them with their, give directions for their lives and gives us clues to the diversity between them. However I use my experiences as a young student and teacher and school experiences and the readings of authors such as CORTI, CATANI, DAYRELL, FREITAS, MCLAREN, PAES, SPÓSITO, TOSTA and others, to solve the contentions in school life that often does not allow young people feel part of the educational process. This research aims to investigate how the graffiti, capoeira and the group of jokes have made part of the culture among the youth in a public1 school in the city of Belo Horizonte / MG, are experienced, understood, having seen the possibilities and limits of dialogue with the integrative Physical Education. I have used the qualitative methodology (LUDKE, 1988) guided by a case study. The procedures consisted of interviews, observations, photographs, individual and collective conversations with young people. Making a dialogue among the worlds of the cultures of youth and physical education is indicative of the hegemony of the sports that are expressed in the organization of the resumés and spaces for their experiences. This process makes youth cultures as mere adjuncts of the sport.